ANALISIS KANDUNGAN KUMAN ENTERIK PADA AIR KEMIH - Agus Supriyanto; Noer Moehammadi (The East Java Biological Society, 1995)
This research was conducted in order to know the total late count (TPC) and what kind of enteric bacteria were isolated from urine specimens. Samples were taken from clinical laboratory, and was examinated in the section of microbiology department of Biology, FMIPAUniversitas Airlangga Surabaya. Thirty five samples were examinated. Method of detection of enteric bacteria, carried out in several steps including enrichment, isolation and identification. Identification step, was done using test of fisiology, motility and morphology with the Gram staining. The result showed, that the number of bacteria in urine specimens was 10 x 103 CFU per ml to 296 x 107 CFU per ml and consist of Enterobacter sp., Pseudomonas sp., Klebsiella sp., Serratia sp., Poteus morgagni, Proteus mirabilis, Aeromonas sp. and Escherichia coli.